The influence of the target language listening exposure in the listening scores of the Advanced English II students, during the first semester, 2016 at the Foreign Language Department of the University of El Salvador - Espinoza Vásquez, Mireya Guadalupe; Guardado Vásquez, Liliana Rosibel; Aguilar Moz, Yoselin Guadalupe (2024)
For more than six decades now, research and practice in English language teaching has identified the “four skills” -listening, speaking, reading and writing- as of paramount importance. The human race has fashioned two forms of productive performance, oral and written, and two forms of receptive performance, aural (or auditory) and reading. The integration of the four skills gives students a chance to diversify their efforts in more meaningful tasks. (Vides, 2010) However, acquiring listening skills can be frustrating for some students. For some time, listening was regarded as a “passive” or “receptive” skill and, consequently, not particularly crucial as a skill area to be taught. Researchers then began to recognize the importance of listening and its role in comprehensible input (Krashen, 1982), and attention to an adoption of newer comprehension-based methodologies brought the issue to the fore. Listening became a skill to be reckoned with and its key position in communication recognized (Feyten, 1991; Omaggio Hadley, 2001). In the communicative approach to language teaching, this means teachers modelling listening strategies and providing listening practice in authentic situations: those that learners are likely to encounter when they use the language outside the classroom. Given the importance of listening in language learning and teaching it is essential to give to the learners the opportunity to develop and improve their listening skills not only in the classroom, but outside the classroom as well.